Radular morphology of Zidona dufresnei (Neogastropoda: Volutidae) and an analysis of its variability along the distributional range. Issue 3 (15th March 2016) - Medina, Alonso I.; Romero, M. Alejandra; Narvarte, Maite A.
ABSTRACT: The radular morphology of Zidona dufresnei was studied by optical and scanning electron microscopy. We analysed the variability among and within three populations distributed along the southwestern Atlantic Ocean coast, considering the hypothesis that the isolation among populations favours adaptive phenotypic variation, which is also expressed at the radular level. Populations selected for this study differ in their maximum individual size, growth rate, size and age at maturity, and fecundity. This study provides the first analysis of the interpopulational variability of the radula of Zidona dufresnei and the first description of its morphology. Zidonia dufresnei exhibited a rachiglossate radulae composed of rows of tricuspid teeth (radular formula: 0+R+0). No differences in tooth shape among populations and sexes were observed. However, significant interpopulational differences in the height of the rachidian cusp and total length of the radula were detected. Specimens from San Antonio Bay showed the lowest values for all radular variables. Positive significant relationships between total shell length and the height of the rachidian cusp and total length of the radula were found, while the number of rows remained relatively constant regardless of size. The larger morphotypes had a longer radula because of an increase in the height of the rachidian cusp. No sexual dimorphism was observed in any morphometric variables of the radula. The results suggest that populations distributed along the Argentine Sea are homogeneous for radular morphology, despite the differences in life history traits, which may be linked to a similarity in feeding habits across populations.